Becoming a Revolutionary : The Deputies of the French National Assembly and the Emergence of a Revolutionary Culture (1789-1790) - Tackett, Timothy (Book collections on Project MUSE., 2014)
Here Timothy Tackett tests some of the diverse explanations of the origins of the French Revolution by examining the psychological itineraries of the individuals who launched it--the deputies of the Estates General and the National Assembly. Based on a wide variety of sources, notably the letters and diaries of over a hundred deputies, the book assesses their collective biographies and their cultural and political experience before and after 1789. In the face of the current ""revisionist"" orthodoxy, it argues that members of the Third Estate differed dramatically from the Nobility in wealt